Conceptual Thoughts of Science and Religion Perspective of Zakaria Ar-Razi - Muhammad Afiq Fikri (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2023)
This paper will discuss one Muslim philosopher who has a strong identity as a Muslim philosopher. He is Zakaria Ar-Razi, in this paper, we will discuss Ar-Razi's biography, his works, and his thoughts. One of Ar-Razi's roles in the development of Islamic philosophy is to give a special style to Islamic philosophy regarding the concept of prophecy which has never been discussed in previous philosophies. This research is library research. The research method contains theories that are relevant to research problems. Ar-Razi is a Muslim scientist and philosopher who has made major contributions to the world of philosophy. Ar-Razi with his naturalistic rational view is also a strong identity about the existence of Islamic philosophy. His ideas on the concept of humans and humanity both physically and psychologically as well as his belief in reason in humans as individuals or groups of social beings led Ar-Razi to the naturalism discourse space. The strong identity conveyed by Ar-Razi is not to reject theological or metaphysical foundations regarding the existence of God, because Ar-Razi himself is still a Muslim who believes in the power of Allah SWT. However, this identity is more to Ar-Razi's efforts to reach the truth using a rationalist and philosophical approach rather than using a theological approach.